2010
DOI: 10.1021/jf100274g
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Effects of Apple Peel Polyphenols against Helicobacter pylori

Abstract: The inhibitory effects of a standarized apple peel polyphenol-rich extract (APPE) against Helicobacter pylori infection and vacuolating bacterial toxin (VacA) induced vacuolation were investigated. Apple peel polyphenols significantly prevented vacuolation in HeLa cells with an IC(50) value of 390 microg of gallic acid equivalents (GAE)/mL. APPE also displayed an in vitro antiadhesive effect against H. pylori. A significant inhibition was observed with a 20-60% reduction of H. pylori attachment at concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 50 publications
0
34
0
2
Order By: Relevance
“…Meanwhile, an apple peel extract showed to inhibit the attachment of H. pylori to HeLa cells by 80% at 10 mg/ml (Pastene et al, 2010).…”
Section: Pelargonium Sidoides (Eps® 7630) Inhibited the Adhesion To Amentioning
confidence: 99%
“…Meanwhile, an apple peel extract showed to inhibit the attachment of H. pylori to HeLa cells by 80% at 10 mg/ml (Pastene et al, 2010).…”
Section: Pelargonium Sidoides (Eps® 7630) Inhibited the Adhesion To Amentioning
confidence: 99%
“…Pastene et al [101] investigated the inhibitory effects of a standardized apple peel polyphenol-rich extract ( Malus pumila Mill., cited as Malus domestica ) against H. pylori infection and vacuolating bacterial toxin (VacA)-induced vacuolation and found that the preparation significantly prevented vacuolation in HeLa cells with an IC 50 value of 390 μg gallic acid equivalents (GAE)/mL and an in vitro anti-adhesive effect against H. pylori . A significant inhibition was also stated with 20–60% reduction of H. pylori attachment at concentrations between 0.250 and 5 mg GAE/mL.…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…The second study, by Gottland and colleagues in Chile, showed that administration of cranberry juice for three weeks inhibited H. pylori about 15% of asymptomatic, colonized children, and that in most subjects who became negative (as measured by UBT), the clearing effect did not persist following cessation of consumption [80]. Furthermore, grape skin/seed extracts and wine preparations [128], (recently reviewed by Friedman [127]), pomegranate fruit and ellagic acid-rich juice (recently reviewed by Colombo [52]), apple [126], and Rubus idaeus and R. occicentalis fruit [154], have all been shown to have antimicrobial activity against H. pylori in vitro . Whereas animal models have been used to demonstrate efficacy of some of these fruit products, no trials currently listed on the USA government website ClinicalTrials.gov, propose to evaluate effects on H. pylori colonization.…”
Section: Foods and Dietary Ingredients With Activity Against H Pymentioning
confidence: 99%